Complete mitogenome of “pumpo” (Bos taurus), a top bull from a Peruvian genetic nucleus, and its phylogenetic analysis - Estrada Cañari, Richard (2024)
The mitochondrial genome of Pumpo (Bos taurus), a prominent breed contributing to livestock farming, was sequenced using the Illumina HiSeq 2500 platform. Assembly and annotation of the mitochondrial genome were achieved through a multifaceted approach employing bioinformatics tools such as Trim Galore, SPAdes, and Geseq, followed by meticulous manual inspection. Additionally, analyses covering tRNA secondary structure and codon usage bias were conducted for comprehensive characterization. The 16,341 base pair mitochondrial genome comprises 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. Phylogenetic analysis places Pumpo within a clade predominantly composed of European cattle, reflecting its prevalence in Europe. This comprehensive study underscores the importance of mitochondrial genome analysis in understanding cattle evolution and highlights the potential of genetic improvement programs in livestock farming, thus contributing to enhanced livestock practices.